Tecnologie, lingua, cittadinanza Percorsi di inclusione dei migranti nei CPIA - Floreancig, Paola (La melagrana - Open Access, 2018)
"The publication documents the experience of action research conducted by the four Provincial Centers for Adult Education (CPIA) of Friuli Venezia Giulia as part of an integrated program of national and international actions, aimed at strengthening the competence of teachers in the use of technologies to create more inclusive and flexible learning environments. The research process, supervised by the University of Udine, has offered teachers not only an opportunity for professional reflexivity, but also the opportunity to participate in an extended professional community of practices."